KARAKTERISTIK FISIK DAN KIMIA PEMPEK KIJING (Pilsbryoconcha sp.) - Asriyatul Hidayah; Susi Lestari; Rodiana Nopianti (Universitas Sriwijaya, 2014)
The objective of this research was to investigate the physical and chemical characteristics of bivalvia pempek (Pilsbryoconcha sp.) by using fasting pre-treatment bivalvia to the raw material and different pempek formulation. This research was conducted on February until July 2014 at the Laboratory of Fishery Product Technology, Chemical Laboratory of Technology of Agricultural, Faculty of Agriculture, and Bioprocess Laboratory of Department of Chemical Engineering, Faculty of Engineering, Sriwijaya University. The Factorial Randomized Block Design was used with two treatment factors that were repeated twice. The treatment factors were consisted of pre-treatment to the bivalvia (without fasting and fasting for 24 hours) and comparison ofÂ the composition of bivalvia meat and tapioca flour (1:2, 1:1, and 2:1). Parameters observed were physical analysis (gel strength and degree of white) and chemical analysis (water content, ash, protein, fat, and carbohydrate). The results of this research showed that average value of gel strength of bivalvia pempek ranged from 208.20 gf to 463.70 gf and degree of white percentage ranged from 45.47% to 51.33%. The average value of the water content ranged from 85.50% to 84.20%, ash content from 0.55% to 0.90%, protein content from 3.82% to 7.31%, fat content from 1.26% to 1.91%, and carbohydrate content from 9.83% to 12.05%. The best treatment was fasting pre-treatment by using water for 24 hours with a ratio 50% of bivalvia meat and 50% of tapioca flour (1:1)